Promoting Factors for Employee Motivation in Nepalese Commercial Banks - Maharjan, Pushpa (PYC Nepal Journal of Management, 2024)
This paper examines the promoting factors for employee motivation in Nepalese commercial banks. The study is based on primary data with 386 responses from 14 banks and used the descriptive research design based on the survey. The self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that monetary rewards lead the employees to attract for best performance and is one of the most influential means of motivating employees to increase the production of the banks. Training, leadership, job enrichment, work environment and employee motivation are positively correlated with organizational performance; the study shows that employee motivation achieved the highest positive correlation with organizational performance.